Mitochondrial genome sequence of the protist Ancyromonas sigmoides Kent, 1881 (Ancyromonadida) from the Sugluk Inlet, Hudson Strait, Nunavik, Québec - Gastineau, Romain; Harðardóttir, Sara; Guilmette, Caroline; Lemieux, Claude; Turmel, Monique; Otis, Christian; Boyle, Brian; Levesque, Roger C.; Gauthier, Jeff; Potvin, Marianne; Lovejoy, Connie (Frontiers in Microbiology, 2023)
There is little information on evolutionarily ancient eukaryotes, often referred to as basal eukaryotes in Arctic waters and despite earlier work in the Russian White Sea, few have been reported. Following a shotgun sequence survey of diatom cultures from Sugluk Inlet off Hudson Strait in Northern Québec, we obtained the complete mitochondrial genome and operon of nuclear ribosomal RNA genes from a strain matching that of Ancyromonas sigmoides Kent, 1881. The sequence of the mitogenome retrieved was 41,889 bp long and encodes 38 protein coding genes, 5 non-conserved open reading frames, 2 rRNA and 24 tRNA genes. The mitogenome has retained sdh2 and sdh3, two genes of the succinate dehydrogenase complex, which are sometimes found among basal eukaryotes but seemingly missing among the Malawimonadidae, a lineage sister to Ancyromonadida in some phylogenies. The phylogeny inferred from the 18S rRNA gene associated A. sigmoides from Sugluk Inlet with several other strains originating from the Arctic. The study also unveiled the presence in GenBank of a metagenomic sequence ascribed to bacteria but which is clearly a mitochondrial genome with a gene content highly similar to those of A. sigmoides, including for the non-conserved open reading frames. After re-annotation, a phylogeny was inferred from mitochondrial protein sequences and it strongly associated A. sigmoides with the misidentified organism, with the two being possibly conspecific or sibling species as they are more similar to one another than to species of the genus Malawimonas.